Bulking agent treatment of incontinent catheterizable channels in pediatric patients and young adults - Jaakkola, Pyry; Pakkasjärvi, Niklas; Mäkelä, Eija; Taskinen, Seppo (Elsevier BV, 2025)
Background: Catheterizable continent channels (CCC) provide means for urinary continence when urethral catheterization is not feasible. However, some patients present with stomal incontinence warranting further interventions. The purpose of this study is to evaluate the effectiveness of endoscopic injection (EI) of bulking agent (Deflux©) as a minimally invasive treatment for CCC incontinence and to explore patient-specific variables influencing outcomes in a pediatric cohort.
Methods: Hospital's pediatric urology procedure registry was retrospectively reviewed to identify all patients with a CCC and at least one EI of bulking agent for the leakage of the stoma at our institution between 2001 and 2021. The postoperative outcomes were assessed three months after the procedure and annually thereafter.
Results: A total of 21 children and young adults were included with CCC indications including neurogenic bladder (n = 13), bladder or cloacal exstrophy (n = 5) and other conditions (n = 3). The most common channel type was appendicovesicostomy (n = 7) followed by Monti tube (n = 5), spiral Monti (n = 3), ureter (n = 3), and other types (n = 3). The median age at first EI was 9.7 years (IQR 8.2-15.1) with a median follow-up time of 4.0 years (IQR 1.2-6.7). At follow-up, 11 patients (52 %) achieved continence. Surgical correction was ultimately required in nine patients (43 %) due to incontinence and in three patients for other reasons. No patient (0 %) experienced long term benefit from >1 injections.
Conclusion: Endoscopic injections offer a minimally invasive option and can be considered a first-line approach for treating CCC incontinence. However, surgical correction remains necessary for some patients. In our material, re-injections were ineffective.